Psychosocial factors that mediate the association between mode of birth and maternal postnatal adjustment: findings from a population-based survey - Alderdice, F; Henderson, J; Opondo, C; Lobel, M; Quigley, M; Redshaw, M (BioMed Central, 2019)
Background: Mode of birth has been found to be associated with maternal postnatal adjustment with women who have Caesarean Sections (CS) thought to be at higher risk of emotional distress. However the relationship is complex and studies have demonstrated mixed findings. The aim of this study is to evaluate a model that explores the direct relationship between mode of birth and postnatal maternal adjustment at 3 months and indirect relationships through psychosocial variables. Methods: A secondary analysis of a population-based survey conducted in England, UK in 2014. The analysis included primiparous women with singleton babies who provided information about mode of birth (n = 2139). Results: Maternal postnatal adjustment, as measured by Maternal postnatal wellbeing and Satisfaction with care during labour and birth, varied by mode of birth. Women who had an unplanned CS had the poorest postnatal adjustment. Mode of birth was not associated with Maternal/infant sense of belonging. Four out of the five proposed mediation variables (Perceived control, Maternal expectation, Support in labour, How long until the mother held her baby), showed partial mediation of the relationship between mode of birth and both Maternal postnatal wellbeing and Satisfaction with care during labour and birth. The strongest mediator was Perceived control and the only variable not to show a significant mediation effect was Health of the infant at 3 months. Conclusions: Birth by unplanned, but not planned, caesarean section was associated with poorer maternal adjustment and instrumental birth was associated with lower maternal satisfaction with labour and birth. These relationships were found to be partially mediated by psychosocial variables. Psychosocial interventions in the perinatal period should be considered to optimise maternal postnatal adjustment.